2022
DOI: 10.1038/s41416-022-02061-5
|View full text |Cite
|
Sign up to set email alerts
|

Dual [68Ga]DOTATATE and [18F]FDG PET/CT in patients with metastatic gastroenteropancreatic neuroendocrine neoplasms: a multicentre validation of the NETPET score

Abstract: Background Gastroenteropancreatic neuroendocrine neoplasms (GEPNENs) are heterogeneous in clinical course, biology, and outcomes. The NETPET score predicts survival by scoring uptake on dual [68Ga]DOTATATE and [18F]FDG PET/CT scans. We aimed to validate previous single-centre findings in a multicentre, international study. Methods Dual scans were assigned a NETPET score of P1 (DOTATATE positive/FDG negative), P2–4 (DOTATATE positive/FDG positive), or P5 (D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 19 publications
2
32
0
Order By: Relevance
“…Furthermore, the score correlated with WHO 2010 histological grade ( p < 0.00001) [ 18 ]. Some years later, the same group of authors validated the grading system in a bigger cohort of 319 metastatic/unresectable gastroenteropancreatic (GEP) NET patients, confirming its prognostic value in terms of OS and time-to-progression as well as with the histological grade [ 43 ]. The impact of NETPET was subsequently evaluated by other studies, and its potential use as a prognostic marker was confirmed [ 44 , 45 ] even in patients with bronchial neuroendocrine neoplasms (NENs) [ 46 ].…”
Section: Research Strategy Resultsmentioning
confidence: 99%
“…Furthermore, the score correlated with WHO 2010 histological grade ( p < 0.00001) [ 18 ]. Some years later, the same group of authors validated the grading system in a bigger cohort of 319 metastatic/unresectable gastroenteropancreatic (GEP) NET patients, confirming its prognostic value in terms of OS and time-to-progression as well as with the histological grade [ 43 ]. The impact of NETPET was subsequently evaluated by other studies, and its potential use as a prognostic marker was confirmed [ 44 , 45 ] even in patients with bronchial neuroendocrine neoplasms (NENs) [ 46 ].…”
Section: Research Strategy Resultsmentioning
confidence: 99%
“…Patients were categorised into three cohorts by the so‐called ‘NETPET’ score (P1, P2–4, and P5), representing SST‐positive/FDG‐negative disease, SST‐positive/FDG‐positive disease, and SST‐negative/FDG‐positive disease, respectively). The authors reported that FDG‐positivity (P2‐5) was present in 73% of all cases, while SST‐expression was lacking (P5) in 12% overall but in none, 10% and 41% of G1, G2, and G3 NEN, respectively 11 . These data should, however, be interpreted with caution.…”
Section: Discussionmentioning
confidence: 95%
“…Besides cost and availability, major arguments against the use of FDG PET/CT in NEN patients are that it may be negative in lower‐grade tumours and that it may not impact management (in patients already studied with SST PET/CT and diagnostic CT/liver MRI). A recently published study included 319 metastatic/unresectable GEP (G1, G2, G3) NEN patients, studied with both SST and FDG PET/CT 11 . Patients were categorised into three cohorts by the so‐called ‘NETPET’ score (P1, P2–4, and P5), representing SST‐positive/FDG‐negative disease, SST‐positive/FDG‐positive disease, and SST‐negative/FDG‐positive disease, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…The NETPET score, a 5-point scoring system for dual PET reporting in subjects with metastatic NENs, summarises the information provided by the two modalities into a single parameter. The NETPET score correlated with histological grade ( p < 0.001), and importantly it was significantly associated with overall survival and time to progression on univariate and multivariate analysis ( p < 0.01) ( 165 ).…”
Section: Future Perspectives In Neuroendocrine Neoplasms Diagnosticsmentioning
confidence: 99%